Utility of the precision cut lung slice model to investigate airway smooth muscle contraction - Fox, Jane (2011)
Asthma is characterised by airway remodelling and an increase in airway resistance. A greater understanding of the mechanisms involved in airway inflammation and airway hyper-responsiveness (AHR) may highlight therapeutic opportunities for asthma. This study initially aimed to optimise the preparation of precision cut lung slices (PCLS) in mouse and pig to investigate the influence of calcium (Ca2+) homeostasis on airway smooth muscle (ASM) contraction as a prelude to human studies. The PCLS technique was then applied to a murine model of allergic airway disease to explore the inflammatory process and pathogenesis of airway hyper-reactivity in sensitised mice.